Cody

Problem 15. Find the longest sequence of 1's in a binary sequence.

Solution 1851565

Submitted on 18 Jun 2019 by Xinyu Xu
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

Test Suite

Test Status Code Input and Output
1   Pass
x = '0'; y_correct = 0; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 0 y = 0 a = 0 y = 0

2   Pass
x = '1'; y_correct = 1; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 1 y = 1

3   Pass
x = '01'; y_correct = 1; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 0 y = 0 a = 1 y = 1

4   Pass
x = '10'; y_correct = 1; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 1 y = 1 a = 0 y = 1

5   Pass
x = '00'; y_correct = 0; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 0 y = 0 a = 0 y = 0 a = 0 y = 0

6   Pass
x = '11'; y_correct = 2; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 2 y = 2

7   Pass
x = '1111111111'; y_correct = 10; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 10 y = 10

8   Pass
x = '100101011111010011111'; y_correct = 5; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 1 y = 1 a = 0 y = 1 a = 1 y = 1 a = 1 y = 1 a = 5 y = 5 a = 1 y = 5 a = 0 y = 5 a = 5 y = 5

9   Pass
x = '01010101010101010101010101'; y_correct = 1; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 0 y = 0 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1

10   Pass
x = '0101010111000101110001011100010100001110110100000000110001001000001110001000111010101001101100001111'; y_correct = 4; assert(isequal(lengthOnes(x),y_correct))

y = 0 a = 0 y = 0 a = 1 y = 1 a = 1 y = 1 a = 1 y = 1 a = 3 y = 3 a = 0 y = 3 a = 0 y = 3 a = 1 y = 3 a = 3 y = 3 a = 0 y = 3 a = 0 y = 3 a = 1 y = 3 a = 3 y = 3 a = 0 y = 3 a = 0 y = 3 a = 1 y = 3 a = 1 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 3 y = 3 a = 2 y = 3 a = 1 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 2 y = 3 a = 0 y = 3 a = 0 y = 3 a = 1 y = 3 a = 0 y = 3 a = 1 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 3 y = 3 a = 0 y = 3 a = 0 y = 3 a = 1 y = 3 a = 0 y = 3 a = 0 y = 3 a = 3 y = 3 a = 1 y = 3 a = 1 y = 3 a = 1 y = 3 a = 0 y = 3 a = 2 y = 3 a = 2 y = 3 a = 0 y = 3 a = 0 y = 3 a = 0 y = 3 a = 4 y = 4